(untitled) (Nuntius Antiquus, 2017)
If nowadays, in the analitycal tradition, philosophy’s key feature is logic argument, in Antiquity, philosophy could embrace rhetoric and a distinct way of life. In this paper, I analyse two conceptions of philosophy, presented by two middle platonic philosophers: Alcinous, author of the Didascalics, and Maximus of Tyre, who wrote the Dialéxeis. As a part of the same philosophical movement, their views are, in some ways, similar: both authors consider philosophy as a form of knowledge of things human and divine that has ethic consequences. But, if Alcinous’ philosophical way of life is the theoretikós bíos,Maximus’ ideal is the philosophical orator, which is possible for him because of his notion of the polyphony of philosophy.